Uptake, translocation, and physiological effects of hematite (α-Fe2O3) nanoparticles in barley (Hordeum vulgare L.). (November 2020) - Tombuloglu, Huseyin; Slimani, Yassine; AlShammari, Thamer Marhoon; Bargouti, Muhammed; Ozdemir, Mehmet; Tombuloglu, Guzin; Akhtar, Sultan; Sabit, Hussain; Hakeem, Khalid Rehman; Almessiere, Munirah; Ercan, Ismail; Baykal, Abdulhadi
Abstract: There has been a growing concern with the environmental influences of nanomaterials due to recent developments in nanotechnology. This study investigates the impact and fate of hematite nanoparticles ( α -Fe2 O3 NPs) (∼14 nm in size) on a crop species, barley ( Hordeum vulgare L.). For this purpose, hematite NPs (50, 100, 200, and 400 mg/L) were hydroponically applied to barley at germination and seedling stages (three weeks). Inductively coupled plasma mass spectrophotometry (ICP-MS) along with vibrating sample magnetometer (VSM) techniques were used to track the NPs in plant tissues. The effects of NPs on the root cells were observed by scanning electron microscopy (SEM) and confocal microscopy. Results revealed that α -Fe2 O3 NPs significantly reduced the germination rate (from 80% in control to 30% in 400 mg/L), as well as chlorophyll (36–39%) and carotenoid (37%) contents. Moreover, the treatment led to a significant decline in the quantum yield of photosystem II (Fv/Fm). Leaf VSM analysis indicated a change in magnetic signal for NPs-treated samples compared with untreated ones, which is mostly attributed to the iron (Fe) ions incorporated within the leaf tissue. Besides, Fe content in the roots and leaf had gradually increased by the increasing doses of NPs, which was confirming NPs' translocation to the aerial parts. Microscopic observations revealed that α -Fe2 O3 NPs altered root cell morphology and led to the injury of cell membranes. This study, in the light of our findings, shows that α -Fe2 O3 NPs (∼14 nm in size) are taken up by the roots of the barley plants, and migrate to the plant leaves. Besides, NPs are phytotoxic for barley as they inhibit germination and pigment biosynthesis. This inhibition is probably due to the injury of the cell membranes in the roots. Therefore, the use of hematite NPs in agriculture and thereby their environmental diffusion must be addressed carefully. Graphical abstract: Image 1 Highlights: Hematite NPs ( α -Fe2 O3, ∼14 nm) in doses 50–400 mg/L are phytotoxic for barley. The treatment inhibited the germination and pigmentation (chlorophyll and carotenoids). They cause cell membrane injury and distruption on root morphology. They are up taken by roots and migrated to leaves, which altered the magnetic signals. Changes in magnetic signals is attributed to the Fe ions incorporated within the tissues. Abstract : α-Fe2 O3 NPs (50–400 mg/L) are phytotoxic for barley: reduce germination rate and pigmentation, and cause cell membrane injury. They change the root morphology and magnetic behavior of the tissues.